Effectiveness Of Information Media Against Covid-19 Control In Elementary School Children In Jambi City - Gustomo Yamistada; Jessy Novita Sari; Solihin Sayuti; Rustam Aji Rochmat; Puspita Sari (International Journal of Health Engineering and Technology, 2022)
The government imposed the implementation of the new normal era so that the socio-economic life of the community could run well. New normal is a change in behavior or habits to continue carrying out activities as usual but by always implementing health protocols in the midst of the Covid-19 pandemic. The implementation of health protocols has not been maximally implemented by the community, especially including school children. The implementation of health protocols in controlling Covid-19 needs to be conveyed to students with the right information media so that students understand and want to implement health protocols both at school and activities outside school. Delivery of appropriate extension methods can improve the effectiveness of the information submitted. Media information will be effective if in accordance with the level of audience or recipient of the message. Delivery in adults will be different from the age of children. Media information that attracts attention will add to the understanding of the target group.The purpose of this study is to know the difference in knowledge based on the type of covid-19 prevention and control education media. This study was conducted by conducting Quasi experiments with research design using Pre and Post Test only Design. The results showed 1) there is a significant difference in the difference in knowledge of elementary school children before and after the use of print media to control Covid-19 with p-Value = 0.001. 2). There was a significant difference in the difference in knowledge of elementary school children before and after the use of video media to control Covid-19 with p-Value = 0,000.3). There was a significant difference in the difference in knowledge of elementary school children before and after the use of teaching aids media to control Covid-19 with p-Value = 0.000.